Aplicación de fibras vegetales y plástico PET reciclado en el diseño de láminas decorativas: http://repositorio.ulvr.edu.ec/handle/44000/3637 - Morales Robalino, Lissette Carolina (2019)
This paper presents the process of a decorative handmade sheet, elaborated from the Carludovica Palmata, which represents one of the most high strength vegetal fiber, and from recycled flakes of PET plastic in combination with polyester resin as final presentation. This proposal of construction materials for interiors, borns from the need to reduce the environmental contamination due to the excessive plastic waste, and to support the application of alternative natural materials. In this sense, the proportions of the resin are analyzed in order to find the optimum one for its solidification without compromising the both components. The result of this work shows the elaboration process of a decorative sheet, applicable to translucent elements.